Zapotin (5, 6, 2′, 6′-tetramethoxyflavone) Modulates the Crosstalk Between Autophagy and Apoptosis Pathways in Cancer Cells with Overexpressed Constitutively Active PKCϵ. (17th February 2016) - Toton, Ewa; Romaniuk, Aleksandra; Budzianowski, Jaromir; Hofmann, Johann; Rybczynska, Maria
ABSTRACT: Autophagy is important in the regulation of survival and death signaling pathways in cancer. PKCϵ revealed high transforming potential and the ability to increase cell migration, invasion, and metastasis. Zapotin (5, 6, 2′, 6′-tetramethoxyflavone), a natural flavonoid, showed chemopreventive and anticancer properties. Previously, we reported that downmodulation of induced PKCϵ level by zapotin was associated with decreased migration and increased apoptosis in HeLa cell line containing doxycycline-inducible constitutively active PKCϵ (PKCϵA/E, Ala 159 → Glu). Depending on the genetic and environmental content of cells, autophagy may either precede apoptosis or occur simultaneously. The purpose of this study was to assess the effect of zapotin on autophagy. Increasing concentration of zapotin (from 7.5 µM to 30 µM) caused an inhibition of the formation of autophagosomes and a decline in microtubule-associated protein 1 light chain 3 (LC3) protein levels. The gene expression level of major negative regulator of autophagy was noticeably increased. Moreover, the expression of the pivotal autophagy genes was decreased. These changes were accompanied by alternation in autophagy-related protein levels. In conclusion, our results implied that both the antiautophagic and the proapoptosis effect of zapotin in HeLaPKCϵA/E cells are associated with the protein kinase C epsilon signaling pathway and lead to programmed cell death.